2022
DOI: 10.1097/dss.0000000000003546
|View full text |Cite
|
Sign up to set email alerts
|

Procedure-Related Risk Factors for Surgical Site Infection in Dermatologic Surgery

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
2
10
0
5
Order By: Relevance
“…The statistical analysis included data from one prospective and four retrospective observational studies. 23 Complex wound closure techniques, on the other hand, were associated with a statistically significant increased infection risk. Based on seven observational studies the cumulative rate of wound infection was 7.9% (n = 27/341) after skin graft (RR 2.95; 95% CI 1.37-6.34).…”
Section: Wound Closure Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The statistical analysis included data from one prospective and four retrospective observational studies. 23 Complex wound closure techniques, on the other hand, were associated with a statistically significant increased infection risk. Based on seven observational studies the cumulative rate of wound infection was 7.9% (n = 27/341) after skin graft (RR 2.95; 95% CI 1.37-6.34).…”
Section: Wound Closure Techniquementioning
confidence: 99%
“…A recently published meta-analysis investigated the wound infection rates dependent from the wound closure techniques. 23 Based on eight observational studies, it has been shown that simple wound closure was associated with a significantly lower wound infection risk (RR 0.34; 95% CI 0.25-0.46). Wounds that underwent secondary healing did not show an altered infection risk according to the meta-analysis (RR 1.82; 95% CI 0.40-8.35).…”
Section: Wound Closure Techniquementioning
confidence: 99%
“…Wunden, die sekundär heilten, zeigten gemäß der Metaanalyse kein verändertes Infektionsrisiko (RR 1,82; 95% KI 0,40–8,35). In die statistische Analyse flossen Daten einer prospektiven und von vier retrospektiven Beobachtungsstudien 23 . Komplexe Wundverschlusstechniken waren hingegen mit einem statistisch erhöhten Infektionsrisiko verbunden.…”
Section: Eingriffsbezogene Risikofaktoren Für Die Entwicklung Postope...unclassified
“…Eine kürzlich veröffentlichte Metaanalyse untersuchte die Wundinfektionsraten verschiedener Verschlusstechniken. 23 Hierbei zeigte sich anhand von acht Beobachtungsstudien, dass einfache Wundverschlüsse mit einem signifikant niedrigerem Wundinfektionsrisiko einhergingen (RR 0.34; 95% KI 0,25-0,46). Wunden, die sekundär heilten, zeigten gemäß der Metaanalyse kein verändertes Infektionsrisiko (RR 1,82; 95% KI 0, 35).…”
Section: Wundverschlusstechnikunclassified
See 1 more Smart Citation